PEMBENTUKAN KARAKTER KEPEDULIAN DALAM BUKU BAHASA INGGRIS SEKOLAH MENENGAH ATAS - elsa ernawati nainggolan; Juliatri Goretti Simamora (Universitas Putera Batam, 2020)
This study aimed at analyzing altruism character in the three English textbooks of senior high school grade X, XI, and XII. Using content analysis, words, phrases, and clauses presenting altruism in the reading text, dialogue, and tasks were examined. The study revealed that in the English textbook of grade X, the altruism aspect indicating ‘pro-social behavior’ and ‘environmental care’ could be frequently found in reading text, dialogue, and task. However, other altruism aspects such ‘giving empathy’ missed in the reading text and ‘reducing inequality’ does not appear in the reading text and dialogue. Meanwhile in the grade XI, ‘giving empathy’ and ‘pro-social behavior’ occur in dialogue and task yet cannot be identified in the reading text. Moreover, ‘environmental care’ only shows up in dialogue and task, while ‘reducing inequality’ is nowhere to be found. In the grade XII, ‘giving empathy’, ‘pro-social behavior’ and ‘environmental care’ could be identified in the reading text, dialogue, and task. Unfortunately, ‘reducing inequality’ aspects only occur in the task. The inconsistent altruism character maintained in the English textbooks used in grade X, XI, and XII of senior high school displayed the missing opportunity to shape students’ altruistic behavior. Considering that senior high school is the stage where students start developing the ability to think logically about abstract ideas, altruism character should be inculcated in the development of English learning material in relevance to students’ intellectual and emotional level.